2001
DOI: 10.1055/s-0037-1615753
|View full text |Cite
|
Sign up to set email alerts
|

Microparticles from Patients with Multiple Organ Dysfunction Syndrome and Sepsis Support Coagulation through Multiple Mechanisms

Abstract: Summary Aim. We investigated the occurrence and thrombin generating mechanisms of circulating microparticles (MP) in patients with multiple organ dysfunction syndrome (MODS) and sepsis. Methods. MP, isolated from blood of patients (n = 9) and healthy controls (n = 14), were stained with cell-specific monoclonal antibodies (MoAbs) or anti-tissue factor (anti-TF) MoAb and annexin V, and analyzed by flow cytometry. To assess their thrombin-generating capacity, MP were reconstituted in normal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
197
2
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 243 publications
(212 citation statements)
references
References 32 publications
11
197
2
2
Order By: Relevance
“…The generated amount of p-nitroaniline was determined at ϭ 405 nm. To convert the observed optical density (OD) to the thrombin concentration, a reference curve was prepared using purified human thrombin (20).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The generated amount of p-nitroaniline was determined at ϭ 405 nm. To convert the observed optical density (OD) to the thrombin concentration, a reference curve was prepared using purified human thrombin (20).…”
Section: Methodsmentioning
confidence: 99%
“…In vivo, microparticles can be found in the systemic circulation; their numbers and cellular origin are dependent on the state of health of the individual. Compared with healthy control subjects, patients at risk of thromboembolic complications have elevated numbers of platelet microparticles in their venous blood (12)(13)(14)(15)(16)(17)(18)(19), and we and other investigators have recently demonstrated the presence of microparticles of nonplatelet origin in the circulation of healthy subjects as well as patients with various clinical conditions (17,(20)(21)(22).…”
mentioning
confidence: 99%
“…Moreover, plasma from patients with APS, MS, or TTP was shown to induce the formation of EMPs from endothelial cells in tissue culture (11,18,19). EMPs exhibit prothrombotic potential, which is mediated by activation of the extrinsic coagulation pathway (i.e., the tissue factor/factor VII-dependent pathway) (11,16,17,(21)(22)(23).…”
Section: Methodsmentioning
confidence: 99%
“…negatively charged phospholipids and tissue factor [1][2][3]. The number of circulating PMV has been shown to increase in various clinical conditions with increased thrombotic risk including coronary artery disease (CAD) [1,4].…”
Section: To the Editormentioning
confidence: 99%